Silent Tumefactive Demyelinating Lesions and Radiologically Isolated Syndrome - Ozgul Ekmekci; Cenk Eraslan (Case Reports in Neurological Medicine)
Demyelinating lesions larger than 2 cm in diameter, with or without edema, are known as tumefactive demyelinating lesions (TDLs). They constitute a rare inflammatory demyelinating disorder of the central nervous system. TDLs are typically characterized by headaches, cortical symptoms such as aphasia, hemiparesis, hemisensory deficits, seizures, and changes in consciousness. TDLs may occur in patients with or without an established diagnosis of MS or may occur as the initial demyelinating event. They may also be observed during follow-up in patients with MS, neuromyelitis optica, acute disseminated encephalomyelitis, or other autoimmune diseases. Differential diagnosis includes brain tumors, abscess, granulomatous diseases, and vasculitis. In some cases, it may be very difficult to distinguish TDLs from a tumor, such that biopsy might be needed. However, no cases of asymptomatic TDLs have yet been reported in the literature. Hence, in this report, we present a case involving an asymptomatic TDL detected incidentally during magnetic resonance imaging in an 18-year-old man. The patient did not develop any symptoms during the 1-year follow-up period. During follow-up, the patient was diagnosed with a radiologically isolated syndrome. TDLs have not previously been identified as radiologically isolated syndrome. Thus, reporting similar cases in the future will help in further understanding this phenomenon.